Motivation, Behavior and Behavioral Intentions of Tourists Traveling in Homestay Communities in Maha Sarakham Province and Kalasin Province - Siribowonphitak, Chaithawat; Sertreart, Patimas; Chaipunha, Suntareeya (Journal of Cultural Approach, 2025)
The purpose of this study was to examine the behavior and intentions of experienced tourists and investigate the motivational aspects of creative experiential tourism based on cultural capital in the communities of Maha Sarakham and Kalasin provinces. The study was a qualitative study that included 400 samples of tourists who visited homestay communities. According to the research findings, the majority of travelers, 74.5 percent, planned to travel or go sightseeing. 67.5 percent of them rarely travel. 37 percent traveled with a group of friends or colleagues, with a total of three persons traveling at 29 percent. Private car travel accounted for 37.25 percent. 27.25 percent traveled for less than two days, while 35.75 percent spent between 1001 and 5000 baht. The majority of them, 52.5%, were aware of tourism attractions through the internet or website. In terms of behavioral intention, the majority of tourists intend to revisit ( = 4.43), followed by referrals to friends or acquaintances at the highest level ( = 4.49). In terms of loyalty, they take tremendous pride in sharing positive experiences at the highest levels ( = 4.24). Furthermore, overall motivational factors are at a high level ( = 3.52), with tourists seeking new and diverse experiences at the highest level ( = 4.52).